THERMAL-EXPANSION OF BRUCITE, MG(OH)2 - Redfern, S; Wood, B (1992)
The lattice parameters of brucite, Mg(OH)2, have been measured between 20 and 310°C at atmospheric pressure. The thermal expansion is strongly anisotropic with a high coefficient of linear expansion (α3) parallel to the z axis. This leads to an overall volume coefficient of expansion (average of 10.9 × 10-5/K) that is several times greater than estimates based on amphiboles and other hydrous minerals. Individual expansion coefficients are α1 = α2 = 1.73 × 10-5 - 0.13 × 10-7T ± 0.17 × 10-5, α3 = 3.23 × 10-5 + 2.65 × 10-7T ± 0.32 × 10-5, and αvol = 6.70 × 10-5 + 2.37 × 10-7T ± 0.67 × 10-5, where T is the temperature between 20 and 310°C. -Authors